Secure Source Coding With a Public Helper - Kittichokechai, Kittipong; Chia, Yeow-Khiang; Oechtering, Tobias J.; Skoglund, Mikael; Weissman, Tsachy (IEEE transactions on information theory, 2016)
We consider secure multi-terminal source coding problems in the presence of a public helper. Two main scenarios are studied: 1) source coding with a helper where the coded side information from the helper is eavesdropped by an external eavesdropper and 2) triangular source coding with a helper where the helper is considered as a public terminal. We are interested in how the helper can support the source transmission subject to a constraint on the amount of information leaked due to its public nature. We characterize the tradeoff among transmission rate, incurred distortion, and information leakage rate at the helper/eavesdropper in the form of the rate-distortion-leakage region for various classes of problems.